2003
DOI: 10.1161/01.cir.0000085995.87982.6e
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral Versus Unilateral Internal Mammary Revascularization in Patients With Diabetes

Abstract: Background-This historical cohort study evaluated the benefit of bilateral internal mammary artery (BIMA) grafts in coronary bypass grafting (CABG) for patients with diabetes. Methods and Results-We performed elective, isolated, primary, multiple CABG using skeletonized internal mammary artery (IMA) grafts for multivessel disease in 1131 patients, 467 (41.3%) of whom had type 2 diabetes mellitus. The early and long-term results were compared between 277 patients with diabetes using single IMA (SIMA) grafts and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(49 citation statements)
references
References 30 publications
(30 reference statements)
1
47
1
Order By: Relevance
“…Similar results have been previously reported in smaller groups of patients with a shorter duration of follow-up. [17][18][19] Unlike those reports, the survival benefit observed here did not appear to be influenced by patient age at the time of surgery. 20 The absence of significant difference in the SWI rate among BIMA patients may represent a type II error that could have become significant with a larger cohort of patients.…”
Section: Discussioncontrasting
confidence: 89%
See 1 more Smart Citation
“…Similar results have been previously reported in smaller groups of patients with a shorter duration of follow-up. [17][18][19] Unlike those reports, the survival benefit observed here did not appear to be influenced by patient age at the time of surgery. 20 The absence of significant difference in the SWI rate among BIMA patients may represent a type II error that could have become significant with a larger cohort of patients.…”
Section: Discussioncontrasting
confidence: 89%
“…Have improvements in perioperative care and medical therapy ameliorated or even eliminated the survival benefits observed? More recent studies with both on-pump 19 and off-pump 17 CABG suggest that these results have been replicable in today's modern surgical era.…”
Section: Dorman Et Al Ima Grafting In Diabetic Patients 2939mentioning
confidence: 90%
“…BIMA use may increase the risk of sternal wound infection, 23,24 especially in patients with diabetes mellitus. 25 However, other studies have shown that the skeletonization technique reduces the risk of wound infection after BIMA use in diabetic patients 26 and that BIMA grafts provide some benefits even in diabetic patients. 26 The indications and contraindications are controversial.…”
Section: Discussionmentioning
confidence: 99%
“…25 However, other studies have shown that the skeletonization technique reduces the risk of wound infection after BIMA use in diabetic patients 26 and that BIMA grafts provide some benefits even in diabetic patients. 26 The indications and contraindications are controversial. However, considering the benefits on long-term outcomes, [7][8][9][10][11] BIMA grafts seem underused in the United States.…”
Section: Discussionmentioning
confidence: 99%
“…This benefit is largely secondary to the use of internal thoracic artery grafts [8,18]. multiple arterial grafts seems to be favorable in these patients [19]. There is recent evidence showing that bilateral internal thoracic artery grafts provide benefits to the long-term survival, although there are no randomized studies to support such findings [20].…”
Section: Introductionmentioning
confidence: 99%